Detection of water leakage location by utilizing optical time domain reflectometery (OTDR) technique [electronic resource] - Salar Qader Hasan, 1986- author; Rosly Abd. Rahman, supervisor; Fakulti Sains (2014)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2014